Raising Standards: Public Works and Industrial Practice in Interwar Ontario - Hull, James (Scientia Canadensis, 2001)
AbstractPublic works and the bodies which build them or contract for their building are important to the history of standards for a variety of reasons. The sheer size, significance and ubiquity of such works, make standards practice important in and of itself. The rigour used in enforcing those standards on contractors and suppliers, while exerting a force for the improvement of industrial practice, also had the secondary effect of favouring those firms which were familiar with and could meet such standards. Public agencies had not just contractual means to enforce their ideas about standards but often regulatory ones as well. Public works standards helped define the state's relationship with the geographical space in which it acted. These issues will be explored using four case studies from Ontario: public roads and buildings, public health regulation and standards for municipal water works, the Hydro-Electric Power Commission of Ontario and finally the City of Toronto.